موسیقی: اسلامی اور سائنسی تناظر میں تحقیقی جائزہ: Music: A Research Review from Islamic and Scientific Perspectives - Syed Muhammad Hanif Agha; Syed Hayatullah; Abdul Tahir (International Research Journal of Arabic and Islamic Studies, 2023)
Islam has discouraged every act that causes a defect in human morals. Man is psychologically compelled to do something for the sake of his own comfort. There is no part of life that is safe from music. Islam clearly dislikes music. The religion of Islam has banned every action that leads to corruption in the society and neglecting the remembrance of Allah. Music is also one of the causes of hypocrisy in the heart and a person's distance from Allah and neglecting prayer. This article an exploratory approach has been adopted which he seeks the bliss of peace. Islam has prohibited any action that would lead to a violation of morals. Music is one of the sources of intellectual chaos and moral disorder. The foundation of Islam consists of Quran and Hadith. The decision to declare an action permissible or impermissible is based on Islamic orders. In today's society, music has developed very well.